An international evaluation of biosecurity management capacity in the seaweed aquaculture industry. (15th February 2022) - Campbell, I.; Mateo, J.; Rusekwa, S.B.; Kambey, C.S.B.; Hurtado, A.; Msuya, F.E.; Cottier-Cook, E.J.
Abstract: Seaweeds form the second largest global aquaculture product in volume, and despite rapid growth of the sector over the last 25 years, production and quality in top producing regions is becoming increasingly limited due to disease and pest outbreaks, the spread of non-native cultivars and the degradation of genetic health due to inbreeding. Most notably, the lack of biosecurity measures leading to disease and pest outbreaks are reported to cause the most significant production losses in the seaweed industry. This study uses the Knowledge, Attitude and Practice (KAP) survey tool to quantify and compare biosecurity cross-culturally, in two major red seaweed producing countries, the Philippines and Tanzania. Both countries have significantly different political contexts and the seaweed sector sits within two very different value chains. Seaweed-based commodities from these countries, however, enters the same international market for carrageenan, a thickening agent used for a variety of products globally. This study uses the KAP survey tool to assess currently-adopted biosecurity control measures and understand how potential policy strategies could be developed on an international scale. Farmers from both producing countries have good biosecurity knowledge. In Tanzania 64% farmers scored Fair or Good, and in the Philippines this was 95%. Corresponding scores in practices were lower, 85% Poor for Tanzania, and 88% Fair for the Philippines, indicating there is a lack of resources for farmers to implement additional practices. The information gathered using the KAP tool in the context of the global seaweed industry can be used to facilitate compromise between science, policy and practice whilst taking into consideration smaller-scale regional challenges. Given the results from the seaweed industry were similar to that of smallholder agricultural sectors, it is suggested that governmental programs to incentivise biosecurity in smallholder rural agriculture could be adapted for the seaweed industry. This study also demonstrates the potential use of the KAP survey, as a tool to accurately compare biosecurity challenges faced by farmers in different aquaculture sectors globally, and to encourage alignment in international approaches to aquaculture biosecurity policies. Highlights: Farmers have good biosecurity knowledge, but lack resources to implement practices. Biosecurity policies should include smallholder and large commercial farms. The KAP tool can facilitate compromise between science, policy and practice. Programs to incentivise biosecurity in smallholder agriculture could be adapted.